SORTING ALGORITHMS REALIZATION AND THEIR FEATURES - Cabuļevs, Ivars; Zorins, Aleksejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
The performance of computers and programs is the most important thing for a user nowadays. Sorting algorithms appeared in the 19th century, but nowadays, developers often forget about the effectiveness of these algorithms and always use only a couple of algorithms, which are not always the best solution for certain tasks. This slows down the performance of certain important applications for professionals as well as for ordinary users. In this work was told and implemented different numerical sorting algorithms. The development environment here was “Microsoft Visual Studio 2017”. Was used the C++ programming language. Knowledge of sorting algorithms will always help you to optimize your program (if there used sorting), which will have a positive impact on user feedback about your application also this knowledge has a positive effect on the thought processes, allowing you to make the right decisions in the shortest time.